A clinical observation study on the effect of needle-free insulin syringe on blood glucose control and well-being index in patients with early-onset type 2 diabetes mellitus - Jin, Xiaolong; Sun, Qiuying; Yue, Chenying; Han, Junming; Zhou, Xinli; Guan, Qingbo; Zhang, Xu (Frontiers in Endocrinology, 2023)
Objective: To explore the effect of using needle-free insulin syringe on blood sugar control and well-being index in patients with early-onset type 2 diabetes mellitus. Methods: A total of 42 patients with early-onset type 2 diabetes mellitus treated with insulin aspart 30 injection in a stable condition in the Endocrinology Department of a tertiary hospital from January 2020 to July 2021 were randomly divided into two groups, one group received insulin pen injections followed by needle-free injections, and the other group received needle-free injections followed by insulin pen injections. Transient scanning glucose monitoring was performed during the last two weeks of each injection modality phase. Comparison of the two injection methods in terms of test indicators and differences in injection site pain scores, the number of red spots on the skin at the injection site and the number of bleeding spots on the skin at the injection site. Results: The FBG of the needle-free injection group was lower than that of the Novo Pen group (p<0.05); the 2-hour postprandial blood glucose of the needle-free injection group was lower than that of the Novo Pen group, but there was no statistical significant difference. The amount of Insulin in the needle-free injector group was lower than that in the Novo pen group, but there was no statistical significant difference between the two groups. The WHO-5 score of the needle-free injector group was higher than that of the Novo Pen group(p<0.05); the pain score at the injection site was lower than that of the Novo Pen group (p<0.05). The number of skin red spots using the needle-free syringe was more than that of the Novo pen group(p<0.05); the number of skin bleeding at the site of injection was similar between the two injection methods. Conclusion: Compared to traditional insulin pens, subcutaneous injection of premixed insulin using a needle-free syringe is effective in controlling fasting blood glucose in patients with early onset type 2 diabetes and is less painful at the injection site. In addition, blood glucose monitoring should be strengthened and insulin dosage should be adjusted in a timely manner.